Chronic Heart Failure and Exercise Intolerance: The Hemodynamic Paradox - Nilsson Jr., Kent R.; Duscha, Brian D.; Hranitzky, Patrick M.; Kraus, William E. (Current Cardiology Reviews, 2008)
Heart failure represents a major source of morbidity and mortality in industrialized nations. As the leading hospital discharge diagnosis in the United States in patients over the age of 65, it is also associated with substantial economic costs. While the acute symptoms of volume overload frequently precipitate inpatient admission, it is the symptoms of chronic heart failure, including fatigue, exercise intolerance and exertional dyspnea, that impact quality of life. Over the last two decades, research into the enzymatic, histologic and neurohumoral alterations seen with heart failure have revealed that hemodynamic derangements do not necessarily correlate with symptoms. This “hemodynamic paradox” is explained by alterations in the skeletal musculature that occur in response to hemodynamic derangements. Importantly, gender specific effects appear to modify both disease pathophysiology and response to therapy. The following review will discuss our current understanding of the systemic effects of heart failure before examining how exercise training and cardiac resynchronization therapy may impact disease course.
Keywords: exercise